Pengaruh Pengawasan dan Komunikasi Interaktif Terhadap Upaya Meningkatkan Disiplin Taruna - Amirullah Amirullah; Sahar Saleh; Sandy Wahyu Purnomo; Henni Sutryani (Alignment:Journal of Administration and Educational Management, 2022)
This study aims to analyze the influence of supervision, communication, and both on cadets' discipline at the Marine Science Training and Education Center (BP2IP) Tangerang. This study used a descriptive-analytical method, the population in this study were all cadet students at BP2IP Tangerang, Banten. This research data use three variables, namely: supervision (X1), communication (X2), and discipline development (Y). The results of this study indicate that the supervision variable carried out by the Tangerang Shipping Science Education and Training Center has an achievement level of 75.10%, the communication variable has an achievement level of 71.93%, and the discipline coaching variable has an achievement level of 75.56%. In conclusion, the supervision, communication, and discipline development for cadets at the Shipping Science Education and Training Center (BP2IP), Tangerang, has a significant effect. It has been carried out well by the Tangerang Shipping Science Training and Education Center.. Keywords: Discipline, Communication, Supervision, Youth.